Sri Lankan diaspora returning 'home' : transnational ways of belonging and being - Laan, Rianne Sujeewa Cornelia Elisabeth (Department of Sociology, 2015)
Return migration is often assumed to be a return to ‘home’ and to be the end of a migration cycle rather than another turn in that cycle. This research examines the links between return migration, transnationalism and (re)integration, among Sri Lankan-born migrants who returned to Sri Lanka. I explore this among a diverse sample of 13 migrants - 7 men and 6 women - consisting of 5 returnees who resided overseas for 10 years or less and 8 returnees who resides abroad more than 10 years before they returned to Sri Lanka. The unstructured interviews were conducted in May, June and July 2014. The findings suggest that the notions of home, ways of belonging and being are experienced by these returnees in different ways. The results reveal that participants migrated at different life-stages and under different circumstances, and their migration experience highlights their transnationality. The term transnationality is used to refer to the participants’ ways of being and belonging in transnational space. According to the research findings, the study identified that (1) return migration is not as permanent as it might suggest - although the participants were firmly established in Sri Lanka, half of the participants were moving back and forth between Sri Lanka and the respective country overseas or have re-migrated to another destination and returned a second time; (2) The notions of home, belonging and being operate simultaneously where multiple attachments in varying degrees develop and change over time and space; (3) Notions of home and belonging are multidimensional; (4) Transnational ways of being are highlighted through return visits and social ties that cross borders; (5) Return visits are significant in (re)integration as social ties are (re)established which enabled participants to find their place in Sri Lanka.